1994
DOI: 10.1021/jm00031a022
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structural Determination, and Biological Activity of 6.alpha.-Hydroxytaxol, the Principal Human Metabolite of Taxol

Abstract: The principal biotransformation product of taxol was found to be identical for human hepatic microsomes, human liver slices, and patient bile samples. We have isolated this metabolite from the bile of a patient given taxol, and we report its structure and its cytotoxicity relative to taxol. The NMR and SIMS data presented here indicate that, in humans, taxol is regiospecifically hydroxylated at the 6-position on the taxane ring and that this hydroxyl is stereospecifically placed trans to the hydroxyl at positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 4 publications
0
38
0
1
Order By: Relevance
“…Moreover, our data indicate that human CYP2C8 was the only P450 involved in the formation of 6␣-OHP. These inhibition studies indicated that the minor paclitaxel metabolite in human microsomes (44% t R of paclitaxel) was apparently not the di-OHP reported by Harris et al (1994a), since it was not sufficiently inhibited by fisetin, although CYP2C8 is involved in di-OHP formation and fisetin was shown to inhibit CYP2C8.…”
Section: Variability In the Formation Of Paclitaxel Metabolitesmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, our data indicate that human CYP2C8 was the only P450 involved in the formation of 6␣-OHP. These inhibition studies indicated that the minor paclitaxel metabolite in human microsomes (44% t R of paclitaxel) was apparently not the di-OHP reported by Harris et al (1994a), since it was not sufficiently inhibited by fisetin, although CYP2C8 is involved in di-OHP formation and fisetin was shown to inhibit CYP2C8.…”
Section: Variability In the Formation Of Paclitaxel Metabolitesmentioning
confidence: 93%
“…The formation of di-OHP results from stepwise catalysis by CYP2C8 and CYP3A4 (Harris et al, 1994b). 6␣-OHP was about 30-fold less active than paclitaxel in tumor cell lines in vitro (Harris et al, 1994a), and C3Ј-OHP, C2-OHP, and baccatin III were also less cytotoxic (Monsarrat et al, 1990). Human CYP1A2, 2E1, 3A4, and 3A5 expressed in Escherichia coli, HepG2, or human lymphoblastoid cells catalyzed only C3Ј-OHP formation (Harris et al, 1994b).…”
mentioning
confidence: 99%
“…As the formation of 6a-hydroxypaclitaxel, approximately 30 times less toxic than the parent compound (Harris et al, 1994), has been shown to be the primary metabolic pathway of paclitaxel metabolism (Taniguchi et al, 2005), it would be reasonable to hypothesize that CYP2C8 polymorphisms could influence the efficacy of paclitaxel treatment. This question has been dealt with by Nakajima et al (2005), who found a 16-fold interindividual variation in the 6a-hydroxypaclitaxel area under the curve (AUC) among 23 female ovarian cancer patients, but apparently no CYP2C8 variant alleles, due to the small study or low frequency of the alleles in Japanese.…”
Section: Cyp2csmentioning
confidence: 99%
“…Taxol is known to be metabolised (Harris et al, 1994b) in the liver and inactivated (Harris et al, 1994a) by cytochrome P450 3A4. Cyclosporin A is also metabolised by cytochrome P450 3A in the liver (Villeneuve et al, 2000) and has been found to block the function of MDR (Twentyman et al, 1987).…”
mentioning
confidence: 99%